2021
DOI: 10.1002/arch.21788
|View full text |Cite
|
Sign up to set email alerts
|

De novo biosynthesis of linoleic acid is widespread in parasitic wasps

Abstract: Linoleic acid (C18:2 Δ9,12 , LA) is an important metabolite with numerous essential functions for growth, health, and reproduction of organisms. It has long been assumed that animals lack Δ12-desaturases, the enzymes needed to produce LA from oleic acid (C18:1 Δ9 , OA). There is, however, increasing evidence that this is not generally true for invertebrates. In the insect order Hymenoptera, LA biosynthesis has been shown for only two parasitic wasp species of the so-called "Nasonia group," but it is unknown wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, studies have shown that linoleic acid intake positively reduces the risk of cardiovascular disease in healthy individuals [ [70] , [71] , [72] ]. Linoleic acid is an essential metabolite of organisms and plays a vital role in growth and reproduction [ [73] , [74] , [75] ]. In this study, the linoleic acid content in fruit oil of ‘Yuji’ in 2020 reached 54.87% ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that linoleic acid intake positively reduces the risk of cardiovascular disease in healthy individuals [ [70] , [71] , [72] ]. Linoleic acid is an essential metabolite of organisms and plays a vital role in growth and reproduction [ [73] , [74] , [75] ]. In this study, the linoleic acid content in fruit oil of ‘Yuji’ in 2020 reached 54.87% ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even those species emerging with rich lipid reserves might synthesize fatty acids later in their lives to replenish ebbing fat reserves due to energy-sapping activities such as foraging and egg laying, without resulting in measurable lipid mass gain. In agreement with this idea, recent studies using stable isotope labelling approaches and chemical analyses by gas chromatography-mass spectrometry (GC/MS) demonstrated that parasitic wasps do not generally lack lipogenesis but are able to convert glucose into fatty acid derivatives [1214]. Wasps fed 13 C-labelled α- d -glucose showed the 13 C-label in fatty acid methyl esters (FAME) obtained by transesterification of their raw lipids.…”
Section: Introductionmentioning
confidence: 97%